2000
DOI: 10.1007/s004310051282
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of interventional occlusion of patent ductus arteriosus with detachable coils: a multicentre experience

Abstract: In our opinion, Cook detachable coils are safe and effective especially in the treatment of persistent ductus arteriosus with a diameter < or = 2.5 mm. Due to the low costs these coils appear to be superior to other devices in this subgroup of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 42 publications
5
20
0
1
Order By: Relevance
“…One of the possible drawbacks of this method may be rather long fluoroscopic exposure required in some patients. In patients with a PDA of <2.0 mm, the mean fluoroscopic time was 18 min and was comparable with other methods 7 . However, in some patients with a PDA of ≥ 2.0 mm, it took approximately 60 min to position two coils in order to make a compact mass.…”
Section: Discussionsupporting
confidence: 62%
“…One of the possible drawbacks of this method may be rather long fluoroscopic exposure required in some patients. In patients with a PDA of <2.0 mm, the mean fluoroscopic time was 18 min and was comparable with other methods 7 . However, in some patients with a PDA of ≥ 2.0 mm, it took approximately 60 min to position two coils in order to make a compact mass.…”
Section: Discussionsupporting
confidence: 62%
“…[15][16][17][18][19] There are only a few reports on the long-term outcome of coil occlusion for PDA. [22][23][24] Our study demonstrated that coil occlusion shows longterm efficacy and safety for patients with PDA. The final occlusion rate was 97.8% without any severe adverse events.…”
Section: Long-term Outcome Of Coil Occlusion In Pda Patientsmentioning
confidence: 54%
“…Wesentlich besser sind demgegenüber die Verschlussraten durch Implantation von replazierbaren Metallspiralen (1, 3, 8,9,19,22,24,25). Berücksichtigt man die Tatsache, dass bei einzelnen Patienten der (21).…”
Section: Diskussionunclassified